Pulkovo coordinates from astrooptical observations - Gorshkov, V.; Miller, N.; Naumov, V.; Prudnikova, E.; Shcherbakova, N. (Кинематика и физика небесных тел, 2005)
The longitude and latitude observations made with two zenith-telescopes and three photoelectric transit instruments of the Pulkovo Observatory during the 20th century were used for coordinates determination. The observations were rereduced in HIPPARCOS reference frame. All known astrometrical reductions and the new model of precession and nutation IAU2000A were used. The longitude (1960–2004) and the latitude (1904–2004) coordinate corrections and their trends were found. The geophysical reasons of detected long-periodical coordinate variations are discussed.